NEOGENE CLIMATE CHANGE AND EMERGENCE OF C4 GRASSES IN THE NAMIB, SOUTHWESTERN AFRICA, AS REFLECTED IN RATITE 13C AND 18O - Ségalen L.; Renard M.; Emmanuel L.; Le Callonnec L.; de Rafélis M.; Lee-Thorp J.A.; Senut B.; Pickford M.; Melice J.-L. (My University, 2006)
Stable light isotopes in ratite eggshells have been shown to be reliable indicators of shifts in climate and environmental conditions in the past. Here, we show that δ18O and δ13C values in fossil and modern ratite eggshells collected in the aeolianite deposits of the southern and central Namib Desert track regional distinctions and global climate shifts throughout the Neogene. δ18O values, although variable, are consistently higher in the central compared to the southern Namib throughout the record. δ18O trends during the Miocene differ for the two regions, but track each other post-Miocene. Throughout the Miocene, δ13C values for ratite eggshells from both the central and southern Namib regions are indistinguishable showing that the flora remained C3 throughout. The overall negative (- 3‰) shift in mean values for Miocene biostratigraphic zones is consistent with the response of C3 photosynthesis to pCO2 shifts from 180 to 320 ppmv as estimated from marine alkenone studies and/or evolution of the δ13C of the atmospheric CO2. Evidence for C4 plants occurs post-Miocene, with the development of the southern, winter rainfall and central/northern, summer rainfall zonation apparent today. These data provide independent corroboration that the expansion of C4-dominated ecosystems after ~ 7 Ma cannot be attributed to a reduction of pCO2 below a 500 ppmv threshold, as earlier proposed. Proliferation of C4 plants in the Namib after ~ 5 Ma and, elsewhere, may be related rather to energy budgets and rainfall seasonality shifts resulting from large-scale atmospheric and oceanic circulation reorganisation. © 2005 Elsevier B.V. All rights reserved.
Keywords: C4 EXPANSION; MIOCENE; NAMIB DESERT; PCO2; RATITE EGGSHELLS; STABLE ISOTOPES; Кайнозой::Неоген::Миоцен; Cenozoic::Neogene::Miocene